Women's experiences of maternal and child health and family planning services in KwaZulu-Natal - S Gatsinzi (AOSIS, 2008)
The increasing recognition that millions of women and children die every year as a result of the poor health of the mother coupled with inadequate care before, during, and after delivery, has highlighted the importance of seeking women's views of health services in order to contribute to improving their health. The purpose of this paper is to shed more light on women's views of health services by exploring their experiences of maternal and child health and family planning services in Cato Manor in KwaZulu- Natal. The findings suggest that the majority of women were unclear about the purpose of antenatal care. Most women had little or no knowledge about the required number of antenatal care visits. In addition, few women reported that they were offered a comprehensive range of contraceptive services during their visit. In most cases, they were only given information on a limited number of family planning methods. However, the majority of women expressed overall satisfaction with the services. Discontent mainly rose from the long waiting period, duration of the consultation and limited contraceptive counselling. In order to ensure sustainable improvements in women's health increasing involvement of men is also important.